Implementasi Manajemen Berbasis Sekolah Dalam Meningkatkan Mutu Pendidikan Di SMPN 04 Paguyaman - Riyanti Ismail; Riska Sya’ban (Pusat Riset dan Inovasi Nasional, 2025)
This research aims to find out how school-based management is implemented in improving the quality of education, find out how to improve the quality of education, find out the obstacles to managing school-based management in improving the quality of education. This research uses a qualitative approach, carried out in the form of descriptive data implementation, the data collection methods used are observation, documentation, interviews. The results of the research carried out are that the process of implementing school-based management in improving the quality of education at SMPN 04 Paguyaman provides freedom to utilize educational resources in the learning process and all activities related to the school environment. The implementation of school-based management in improving the quality of education at SMPN 04 East Paguyaman cannot be separated from obstacles that hinder and support the process of implementing school-based management. Success in implementing school-based management can be seen from the input, process and output of SMPN 04 East Paguyaman